Transfer of radiocaesium (137Cs) to lynx (Lynx lynx) and brown bear (Ursus arctos) in Chernobyl affected areas in Sweden - Chaiko, Yury (SLU/Dept. of Soil and Environment, 2012)
In this study, 137Cs activity concentration was measured in 266 lynxes hunted in early spring during the years 2006-2011 in central and northern Sweden and in 161 bears hunted in the end of August until October during the years 2010 and 2011.